Oceanic maintenance of atmospheric blocking in wintertime in the North Atlantic - Mathews,J; Czaja,A (Climate Dynamics, 2024)
The connection between atmospheric blocking over the North Atlantic and the diabatic influence of the Gulf Stream is investigated using potential vorticity and moist potential vorticity diagnostics in the ERA5 reanalysis data set during wintertime (1979 - 2020). In line with previous research, the reliance atmospheric blocking has on turbulent heat fluxes over the Gulf Stream and its extension, for induction and maintenance, is shown to be significant. The air-sea heat flux generates negative potential vorticity air masses in the atmospheric boundary layer. These air masses subsequently contribute to the block’s negative potential vorticity anomaly at upper levels through ascending motion in the warm conveyor belt. It is shown that the block’s size and frequency partially depends on oceanic preconditioning via anomalous oceanic heat transport and heat content, prior to the blocking event, both of which allow for stronger turbulent heat fluxes. It is further hypothesized that the block feeds back positively on itself through the advection of cold dry air over the Gulf Stream, sustaining this air-sea interaction. This in turn decreases ocean heat content, eventually halting this air-sea interaction and severing the atmospheric block from its maintenance pathway.